Relationship between plasma fi brinogen levels with model of end stage liver disease score in patients with liver cirrhosis - Moch. Abdul Nasir; Neneng Ratnasari; Putut Bayupurnama (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTIntroduction. One of the complications which often occur in the liver cirrhosis is bleeding. Closely associated with weighing of bleeding were disturbance haemostatic homeostasis disorders that commonly associated with impaired liver function. Therefore certain biomarkers are needed to objectively measure the severity of liver cirrhosis. Fibrinogen is one of the clotting factors that can be used to determine the severity of liver cirrhosis.The model of end-stage liver disease (MELD) score is most excellent alternative of the Child-Pugh score. It can be used in patients with liver cirrhosis spacious ranges severity of disease and etiology even in patients whose cirrhosis etiology are not clear. Currently, there was not any data showing the correlation between the level of plasmatic fi brinogen and MELD score in patients with liver cirrhosis. Aims. This study aimed to determine the correlation between level of plasmatic fi brinogen and MELD score in patients with liver cirrhosis.Method. This study was cross-sectionally conducted used consecutive sampling. Study population were eligible patients with liver cirrhosis who visited outpatient and inpatient clinic in the Division of Gastroentero-hepatology, Dr. Sardjito general hospital, between November 2011 to October 2012. Correlation between the level of plasmatic fibrinogen and MELD score was statistically assessed using correlation test with fi nal result stated as correlation coefficient (r).Result. There were 40 subjects that met criteria, 28 male and 12 female, with average age of 53 ± 12,51 years. Etiology of cirrhosis was viral hepatitis B in 16 (40,0%) subjects, hepatitis C in 11 (27,5%) subjects and non viral in 13 (32,5%) subjects. Subjects with ascites were 19 (47, 5%) and without ascites were 20 (52.5%). Bleeding was experienced by 30 (80.0%) subjects while 10 (20,0%) subjects did not present with bleeding. Mean of plasma fibrinogen was 198 ± 102, 89 mg/dl, and mean of the MELD score was 17,05 ± 8.79. Spearman correlation coefficients between fi brinogen and MELD score was r = -0,404 (p = 0,010).Conclusion. There was a negative correlation between plasma fi brinogen and the MELD score in liver cirrhosis patients visiting our local setting.Keywords: liver cirrhosis, fi brinogen, MELD score